1984
DOI: 10.1002/jcp.1041180115
|View full text |Cite
|
Sign up to set email alerts
|

Human megakaryocytic progenitors (CFU‐M) assayed in methylcellulose: Physical characteristics and requirements for growth

Abstract: The basic culture requirements and several physical characteristics were defined for megakaryocytic colony-forming cells (CFU-M) from normal human marrow growing in methylcellulose. Ficoll-hypaque separated mononuclear cells from human marrow gave rise to megakaryocytic colonies in the presence of normal human plasma and phytohemagglutinin-stimulated leukocyte-conditioned medium (PHA-LCM). Their identity as megakaryocytic colonies was confirmed by immunofluorescence staining with a monoclonal antibody to human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
44
0

Year Published

1984
1984
1999
1999

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(47 citation statements)
references
References 27 publications
3
44
0
Order By: Relevance
“…A representative time sequence of colony formation from a single cell to a multilineage colony and the companion May-Grunwald-Giemsa preparation are depicted in Fig. 1 A-D ( 17) suggested that the use of unfrozen human plasma and platelet-poor plasma supports megakaryocyte colony formation better than serum.…”
Section: Resultsmentioning
confidence: 99%
“…A representative time sequence of colony formation from a single cell to a multilineage colony and the companion May-Grunwald-Giemsa preparation are depicted in Fig. 1 A-D ( 17) suggested that the use of unfrozen human plasma and platelet-poor plasma supports megakaryocyte colony formation better than serum.…”
Section: Resultsmentioning
confidence: 99%
“…In the maturation. [14][15][16][17][18][19][20][21][22][23][24][25][26]39,43 Campath-1G is a T lymphocytespecific moAb that is routinely employed to reduce GVHD absence of PICS-J negligible numbers of MK colonies were observed. None of the CM significantly stimulated MK in allogeneic BMT.…”
Section: Effect Of Conditioned Medium Derived From Enriched Populatiomentioning
confidence: 99%
“…Our ation. [19][20][21][22]25,26 We have previously demonstrated that Campath-1G-treated T lymphocytes or purified CD4 + T cells data demonstrate that resting and Campath-1G-treated NK may be involved in the immunomodulation of significantly enhance the number of early burst-forming units (BFU-MK) and late colony-forming units (CFU-MK) megakaryocytopoiesis. Keywords: natural killer cells; Campath-1G; megakaryoderived from BM-non adherent mononuclear cells.…”
mentioning
confidence: 99%
“…The nonadherent low-density marrow mononuclear cells were T-lymphocyte depleted by the E-rosette technique using neuraminidase-treated sheep erythrocytes. The nonadherent T-cell-depleted marrow cells were cultured at a concentration of 5 x 104 cells per ml of a medium (Flow Laboratories) containing 1% methylcellulose, 20% (vol/vol) fetal calf serum [or 25% (vol/vol) human plasma for megakaryocyte colony assays], 1% deionized bovine serum albumin (not used in megakaryocyte colony assay) (Reheis, Phoenix, AZ), i0-4 M 2-mercaptoethanol, and penicillin/streptomycin (14,15). Human urinary erythropoietin, partially purified in our laboratory to a specific activity of 200 units/mg, was added at a concentration of 1 unit/ml on day 4 of culture (16).…”
mentioning
confidence: 99%
“…Phytohemagglutinin-stimulated lymphocyte conditioned medium (PHA-LCM) (15) served as a positive control. Colonies were counted on day 13 (14,15 Trypsin Digestion of the Growth Factor. One milliliter of ECM or ECMa was digested with 50 units of agarose-bound trypsin (Sigma) for 20 min at 30°C.…”
mentioning
confidence: 99%